Influenza virus hemagglutinin and neuraminidase glycoproteins stimulate the membrane association of the matrix protein. - Enami, M (1996)
We have analyzed the mechanism by which the matrix (M1) protein associates with cellular membranes during influenza A virus assembly. Interaction of the M1 protein with the viral hemagglutinin (HA) or neuraminidase (NA) glycoprotein was extensively analyzed by using wild-type and transfectant influenza viruses as well as recombinant vaccinia viruses expressing the M1 protein, HA, or NA. Membrane binding of the M1 protein was significantly stimulated at the late stage of virus infection. Using recombinant vaccinia viruses, we found that a relatively small fraction (20 to 40%) of the cytoplasmic M1 protein associated with cellular membranes in the absence of other viral proteins, while coexpression of the HA and the NA stimulated membrane binding of the M1 protein. The stimulatory effect of the NA (>90%) was significant and higher than that of the HA (>60%). Introduction of mutations into the cytoplasmic tail of the NA interfered with its stimulatory effect. Meanwhile, the HA may complement the defective NA and facilitate virus assembly in cells infected with the NA/TAIL(-) transfectant. In conclusion, the highly conserved cytoplasmic tails of the HA and NA play an important role in virus assembly.